THE USE OF DIGITAL TECHNOLOGIES IN THE EDUCATION OF YOUNG PEOPLE AND ADULTS: REFLECTIONS FROM THE IDEAS OF PIERRE LÉVY - Pereira Dutra Wellwock, Inalva; Staub Araldi, Inês (Revista Gênero e Interdisciplinaridade, 2023)
This article presents a bibliographical contribution on the use of digital technologies in Youth and Adult Education (EJA) and how this modality has been increasingly present in various educational programs and projects. Technological evolution has enabled significant changes in EJA teaching, however, this process still faces important challenges. With regard to the use of digital technologies, it is necessary to consider, firstly, the historical dimensions of EJA, which presents traces of a complex and challenging trajectory, meeting the demands of an adult population seeking to resume or begin their basic education. The use of digital media can be seen as a way to meet this demand, enabling access to content in a flexible way and based on the individual needs of each student. In this sense, Pierre Lévy’s ideas have been fundamental in thinking about the use of technologies in EJA. Author of important concepts such as What is virtual, he presents the internet as a central tool in the construction of a new network society. Teacher training is a fundamental aspect for the success of virtualization at EJA. Educators need to be prepared to take on a mediating role between students and technology, in order to guarantee meaningful learning adapted to the specific needs of each student. In this way, virtualization at EJA, with support from Pierre Lévy, can be seen as an opportunity to democratize access to education and guarantee the formation of a more connected and inclusive society.